Traumatic Massive Cervicothoracic Pneumorrhachis: A Case Report - Ucler, Necati; Albayrak, Serdal; Yildiz, Mustafa; Arici, Lutfu; Kaplan, Metin (Lippincott Williams & Wilkins, 2012)
Pneumorrhachis (PR) after major trauma is a very rare condition. Although rarely reported in literature, PR is a sign of a serious underlying pathology related to head, spinal, thoracic, or abdominal trauma. For this reason it should be considered as important. We present a case with severe head trauma caused by a motor vehicle accident that resulted in pneumocephalus and air in the spinal canal, which extended to both cervical and thoracic spinal canals. Although PR has different mechanisms, we consider that abundant cerebrospinal fluid loss from traumatic skull fractures may facilitate the entry of air into the spaces containing this fluid, as in our case.
Keywords: cerebrospinal fluid; cervicothoracic veretebra; head trauma; pneumorrhachis